Using tag data to assess behaviour, vocal sounds, boat noise and potential effects on Humpback whales (Megaptera novaeangliae) in response to whale watching boats in Skjálfandi Bay (Húsavík), Iceland - Ovide, Belén García, 1990- (2017)
The rapid development of whale watching in Iceland can represent a serious threat to whales during their critical feeding season. Humpback whales (Megaptera novaeangliae) are one of the most desired whales for wildlife encounters. However, little is known concerning potential effects from whale watching. Furthermore, there is little knowledge regarding vocal humpback whales vocalizations in the area. In this study, acoustic tags were attached to seven humpback whales during summers 2013 and 2014 in Skjálfandi Bay, Húsavík, Iceland. Boat noise levels were measured to investigate possible changes in natural behaviour. A customized breath and lunge detector was built and behavioural patterns were described and analysed statistically. Generalized linear models were used to test for changes in mean dive depth, jerk rate, breath rate, vertical speed, dive rate and dive duration before, during and after exposure to boats. Effects of tagging, boat noise intensity and whether boats were just passing or actively approaching were also tested. Whale vocalizations were assessed and described. Upsweep grunts were the most common vocalizations detected and high frequency calls were also registered during the foraging stage.The results included a significant reduction of jerk rate during active boat approaches compared to boat passes, and increase of mean depth during exposure to high noise intensity compared to low noise intensity. No differences were found between the before, during and after phases. Whales responded by diving deeper and performing longer dives when the boat exposure started during the first hour of the record compared to later boat exposures (suggesting a tagging effect). No significant changes were found for breath rate, vertical speed and dive rate. The observed changes in jerk rate and mean depth might indicate a disruption of foraging behaviour. These immediate responses could lead to impacts affecting the energy availability in the long term. Further, the registered levels of boat noise may impair whale ...